The ethics of research related to health care in developing countries. Issue 2 (13th April 2004) - McMillan, J R; Conlon, C
Abstract : A report by the Nuffield Council on Bioethics, contrary to the Declaration of Helsinki, permits most important research initiatives in developing countries. The Ethics of Research Related to Health Care in Developing Countries by the Nuffield Council on Bioethics makes a number of innovative recommendations that depart from codes such as the Declaration of Helsinki. It recommends that standards of care might be relativised to the standard of that nation. It recommends that very good reasons need to be given for not giving post-trial access to medications but recognises that there may be justifiable instances of this. It is the view of the authors that these and other recommendations of the report are sensible pieces of advice given the complexities of the developing world.